Politik Hukum Penempatan TNI Aktif dalam Jabatan Sipil : Antara Kepentingan Negara dan Supremasi Sipil - Salsabil, Hilda Halnum; Abdul Aziz Nasihuddin (Fakultas Hukum Universitas Bangka Belitung, 2025)
The appointment of active TNI (Indonesian National Armed Forces) officers to civilian positions has sparked controversy within Indonesia’s legal and democratic framework. The 1998 Reform Movement emphasized the restriction of military involvement in civilian governance, as stipulated in Law Number 34 of 2004 concerning the TNI. However, legal loopholes allow active-duty officers to occupy civilian posts under certain conditions, as reflected in the appointment of the Cabinet Secretary pursuant to Presidential Regulation Number 148 of 2024. This study analyzes the policy from a legal-political perspective by examining regulatory inconsistencies and the implications for civilian supremacy. The research employs a normative juridical method with political, statutory, and conceptual approaches. The findings indicate that the appointment of active-duty military personnel to civilian positions lacks clear urgency and contradicts the principle of civilian supremacy in a democratic system. Furthermore, this policy reflects a tug-of-war between political stability and the interests of ruling elites, potentially hindering military reform and creating regulatory overlaps. Therefore, clearer and more consistent regulations are needed to maintain the balance between national interests and civilian supremacy within Indonesia’s legal system.